Therapeutic Approach to Neurodegenerative Diseases by Medical Gases: Focusing on Redox Signaling and Related Antioxidant Enzymes. (1st July 2012) - Fujita, Kyota; Yamafuji, Megumi; Nakabeppu, Yusaku; Noda, Mami
Abstract : Oxidative stress in the central nervous system is strongly associated with neuronal cell death in the pathogenesis of several neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, Huntington's disease, and amyotrophic lateral sclerosis. In order to overcome the oxidative damage, there are some protective signaling pathways related to transcriptional upregulation of antioxidant enzymes, such as heme oxygenase-1 (HO-1) and superoxide dismutase (SOD)-1/-2. Their expression is regulated by several transcription factors and/or cofactors like nuclear factor-erythroid 2 (NF-E2) related factor 2 (Nrf2) and peroxisome proliferator-activated receptor- γ coactivator 1 α (PGC-1 α ). These antioxidant enzymes are associated with, and in some cases, prevent neuronal death in animal models of neurodegenerative diseases. They are activated by endogenous mediators and phytochemicals, and also by several gases such as carbon monoxide (CO), hydrogen sulphide (H2 S), and hydrogen (H2 ). These might thereby protect the brain from severe oxidative damage and resultant neurodegenerative diseases. In this paper, we discuss how the expression levels of these antioxidant enzymes are regulated. We also introduce recent advances in the therapeutic uses of medical gases against neurodegenerative diseases.